Avaliação do reparo ósseo na interface osso/implante em ratas com deficiência de estrogênio tratadas com ranelato de estrôncio: análise imunoistoquímica, microtomográfica e por microscopia confocal - Yogui, Fernanda Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The purpose of this study is to evaluate the bone repair process at the bone/implant interface in estrogen deficient rats treated with strontium ranelate by using histological, immunohistochemical, microtomographic and confocal microscopy analysis. Thirty six (36) adult rats were divided into three experimental groups: 12 sham rats (SHAM), 12 ovariectomized rats (OVX) and 12 ovariectomized rats treated with strontium ranelate (Ran-Sr). On day 0, ovariectomy surgery was performed, after 30 days the daily drug treatment with strontium ranelate by gavage was started. After 30 days of medication, the implant surgery was performed on the right and left tibias. The euthanasia occurred 42 and 60 days after the implants were installed, in order to perform the histological analysis of the peri-implant bone repair process; immunohistochemical analysis directed to immunomarkers: RUNX2, ALP, OPN and OCN; microtomographic analysis (micro-CT), for the parameters of BV/TV, BV, Tb.Th, Tb.N, Tb.Sp and Po(Tot); and confocal microscopy evaluation, to determine BIC (bone/implant contact) and NBA (neoformed bone area). Quantitative data from micro-CT and confocal microscopy (BIC and NBA) were subjected to homoscedasticity analysis (Shapiro-Wilk test) to distinguish parametric and nonparametric data. The parametric data was compared by ONE WAY ANOVA test and Tukey post-test, and the significance level was set at p<0.05. In the histological analysis was observed a higher degree of corticalization and maturation of the periimplant bone tissue in the SHAM and Ran-Sr groups, the OVX group presented small bone formation and big amount of adipose tissue. By immunohistochemical, the RUNX2 protein had moderate labeling for SHAM and Ran-Sr and intense for OVX. ALP showed intense immunostaining in SHAM, moderate in Ran-Sr and light in OVX. For OPN, the SHAM and Ran-Sr groups had moderate labeling and the OVX group, light. OCN showed...

Este estudo tem como objetivo avaliar o processo de reparo ósseo na interface osso/implante em ratas com deficiência de estrógeno tratadas com ranelato de estrôncio por meio das análises histológica, imunoistoquímica, microtomográfica e por microscopia confocal. Trinta e seis (36) ratas, adultas, foram divididas em três grupos experimentais: 12 ratas controle (SHAM), 12 ratas ovariectomizadas (OVX) e 12 ratas ovariectomizadas e tratadas com ranelato de estrôncio (Ran-Sr). No dia 0 foi realizada a cirurgia de ovariectomia, após 30 dias foi dado o início ao tratamento medicamentoso com o ranelato de estrôncio por meio de gavagem diariamente, decorrido 30 dias de medicação foi realizada a cirurgia de instalação dos implantes nas tíbias direita e esquerda. A eutanásia foi realizada aos 42 e 60 dias após a instalação dos implantes para realização das análises histológica do processo de reparo peri-implantar; análise imunoistoquímica direcionada para os imunomarcadores: RUNX2, ALP, OPN e OCN; análise microtomográfica (micro-CT), para os parâmetros de BV/TV, BV, Tb.Th, Tb.N, Tb.Sp e Po(Tot); e análise por microscopia confocal para determinar a ELCOI (extensão linear de contato osso/implante) e AON (área óssea neoformada). Os dados quantitativos da micro-CT e microscopia confocal (ELCOI e AON) passaram pela análise de homocedasticidade (teste de Shapiro-Wilk), para distinção dos dados paramétricos e não paramétricos. Os dados paramétricos foram comparados pelo teste ONE WAY ANOVA e pós-teste Tukey, adotou-se o nível de significância p<0,05. Na análise histológica observa-se maior grau de corticalização e maturação do tecido ósseo peri-implantar nos grupos SHAM e Ran-Sr, o grupo OVX apresentou pequena formação óssea e grande quantidade de tecido adiposo. Pela imunoistoquímica, a proteína RUNX2 teve marcação...
Keywords: Osteoporose; Estrôncio; Osseointegração; Osteoporosis